Student-Centered Services: BSOA Students’ Awareness and Satisfaction - Kristine Gamban; Rechienvhel Occiano; Princess Ann Odavar; Maria Joy Iglesia (The Indonesian Institute of Science and Technology Research, 2026)
This study was conducted to evaluate the level of awareness and satisfaction of Bachelor of Science in Office Administration (BSOA) students toward the student-centered services offered by Camarines Sur Polytechnic Colleges (CSPC)–Nabua Campus for the academic year under study. The research assessed students’ awareness and satisfaction across nine service areas, namely: Dean’s Office, Guidance and Counseling Services, Medical Services, Library Services, Registrar’s Office, General Services, Student Affairs and Services, Internet Services, and the Supreme Student Council. The respondents of the study were the 272 BSOA students officially enrolled during the academic year 2025-2026. This study utilized the quantitative descriptive research design, with data gathered through a structured survey questionnaire. The statistical tools used were weighted mean and rank distribution. Findings revealed that the respondents were generally aware of and satisfied with the student-centered services provided by the institution, with most indicators receiving verbal interpretations of “Aware” and “Satisfied.” However, lower ratings were noted in Guidance and Counseling Services, Medical Services, Internet Services, and the Supreme Student Council, particularly in areas related to mental health programs, access to medical services, internet connectivity, and student leadership visibility. Based on the results of the study, an Action Plan and Intervention Program was proposed to enhance the visibility, accessibility, and effectiveness of selected student-centered services. The study concluded that while CSPC demonstrates commendable delivery of student services, continuous improvement in service promotion, accessibility, and inter-office coordination is necessary to further strengthen student engagement and satisfaction.